2021
DOI: 10.3390/cancers13205119
|View full text |Cite
|
Sign up to set email alerts
|

Cell Biology of Giant Cell Tumour of Bone: Crosstalk between m/wt Nucleosome H3.3, Telomeres and Osteoclastogenesis

Abstract: Giant cell tumour of bone (GCTB) is a rare and intriguing primary bone neoplasm. Worrisome clinical features are its local destructive behaviour, its high tendency to recur after surgical therapy and its ability to create so-called benign lung metastases (lung ‘plugs’). GCTB displays a complex and difficult-to-understand cell biological behaviour because of its heterogenous morphology. Recently, a driver mutation in histone H3.3 was found. This mutation is highly conserved in GCTB but can also be detected in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 131 publications
0
11
0
Order By: Relevance
“…GCTB is a locally aggressive and rarely metastasizing neoplasm histologically composed of a mononuclear cellular component (round histiocytes and elongated neoplastic cells) and osteoclastlike giant cells (14). It is still difficult to understand the cell biology of GCTB, that is the interaction of the different cell types, but a generally accepted concept has been described by Forsyth et al (15) recently: there is a crosstalk between m/wt nucleosome H3.3, telomeres and osteoclastogenesis. Extensive studies (16)(17)(18) revealed the mechanism of interaction between the macrophage and osteoclast-like cell populations, which express nuclear factor kappa B (RANK) and the stromal cells, which produce RANK ligand (RANKL).…”
Section: Discussionmentioning
confidence: 99%
“…GCTB is a locally aggressive and rarely metastasizing neoplasm histologically composed of a mononuclear cellular component (round histiocytes and elongated neoplastic cells) and osteoclastlike giant cells (14). It is still difficult to understand the cell biology of GCTB, that is the interaction of the different cell types, but a generally accepted concept has been described by Forsyth et al (15) recently: there is a crosstalk between m/wt nucleosome H3.3, telomeres and osteoclastogenesis. Extensive studies (16)(17)(18) revealed the mechanism of interaction between the macrophage and osteoclast-like cell populations, which express nuclear factor kappa B (RANK) and the stromal cells, which produce RANK ligand (RANKL).…”
Section: Discussionmentioning
confidence: 99%
“…Neoplastic stromal cells express RANKL, a surface marker, which has a pivotal role in the signaling pathway of bone remodeling and in the differentiation of precursors into giant multinucleated osteoclast-like cells, which can be considered activated components, influencing osteoclastogenesis and cell proliferation (tumorigenesis) [ 2 , 22 , 41 ]. RANKL overexpression in the tumoral stroma is associated to OPG negative feedback inhibition and decreased OPG gene expression, whose combination induces osteoclastic giant cell formation by the fusion of macrophagic precursors [ 41 , 45 ]. Furthermore, multinucleated giant cells, stromal cells and monocytic cells produce high levels of matrix metalloproteinase 14 (MMP14), which is responsible for the cleavage of membrane-bound RANKL into soluble RANKL, thus promoting osteoclastogenesis [ 45 , 46 ].…”
Section: Gctb Cytology Histopathogenesis and New Biomarkers In Molecular Targeted Therapy Eramentioning
confidence: 99%
“…RANKL overexpression in the tumoral stroma is associated to OPG negative feedback inhibition and decreased OPG gene expression, whose combination induces osteoclastic giant cell formation by the fusion of macrophagic precursors [ 41 , 45 ]. Furthermore, multinucleated giant cells, stromal cells and monocytic cells produce high levels of matrix metalloproteinase 14 (MMP14), which is responsible for the cleavage of membrane-bound RANKL into soluble RANKL, thus promoting osteoclastogenesis [ 45 , 46 ].…”
Section: Gctb Cytology Histopathogenesis and New Biomarkers In Molecular Targeted Therapy Eramentioning
confidence: 99%
“…Mechanisms related to TPE-OLD also have been reported recently based on a study of giant cell tumor of bone (GCTB), which is a rare bone tumor [ 92 ]. The authors suggested that the reactivation of h TERT transcription is related to the length of the telomeres, suggesting that TPE-OLD may be involved in the acquisition of telomerase reactivation during the development of GCTB.…”
Section: Telomere Position Effect-over Long Distances (Tpe-old)mentioning
confidence: 99%